2022
DOI: 10.1021/acschemneuro.2c00234
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from microRNA-21 Overexpressing Neural Progenitor Cells Prevent Hearing Loss from Ischemia-Reperfusion Injury in Mice via Inhibiting the Inflammatory Process in the Cochlea

Abstract: Both exosomes derived from neural progenitor cells (NPCs) can suppress inflammation. Whether exosomes derived from miR-21-transfected NPCs (miR-21-Exo) could be utilized to alleviate hearing loss is investigated. NPCs were transfected with lentiviral vectors overexpressing miR-21, and miR-21-Exo was purified. Morphology and exosome membrane markers were examined with nanoparticle tracking analysis, transmission electron microscopy, and Western blot. After incubation with different concentrations of miR-21-Exo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Because of the low transduction rate of adeno-associated virus in the cochlea, researchers have designed AAV-inner ear for gene delivery in the mouse cochlea and achieved a good therapeutic effect (Tan et al, 2019 ). RNase readily degrades miRNA in the plasma; thus, researchers have used exosomes produced by lentiviral overexpression of miR-21 as a carrier to deliver miR-21 to the inner ear, preventing hearing loss from ischemia-reperfusion (Hao et al, 2022 ). Injecting miR-375 agomir can alleviate nasal mucosa inflammation in allergic rhinitis mice (Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the low transduction rate of adeno-associated virus in the cochlea, researchers have designed AAV-inner ear for gene delivery in the mouse cochlea and achieved a good therapeutic effect (Tan et al, 2019 ). RNase readily degrades miRNA in the plasma; thus, researchers have used exosomes produced by lentiviral overexpression of miR-21 as a carrier to deliver miR-21 to the inner ear, preventing hearing loss from ischemia-reperfusion (Hao et al, 2022 ). Injecting miR-375 agomir can alleviate nasal mucosa inflammation in allergic rhinitis mice (Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hao et al discovered that exosomes derived from miR-21-overexpressing NSCs could prevent hearing loss from IRI by inhibiting the inflammatory process in the mouse cochlea. 306 This was evidenced by a reduced auditory brainstem response threshold, upregulated IL-10 and downregulated TNF-α and IL-1β.…”
Section: Otorhinolaryngology and Head And Neck Surgery And Sc-exo The...mentioning
confidence: 99%
“…In other words, some preclinical studies have not yet developed into clinical trials. These include, but are not limited to, exosome therapy for fracture 333 spinal cord injury 334 traumatic brain injury 335 acute liver injury 336 and hearing loss 304,306 which might serve as future directions for exosome therapy-related clinical trials.…”
Section: From Preclinical Studies To Clinical Trials Of Exosome Therapymentioning
confidence: 99%
“…However, proteomic analysis showed a significant increase in protein expression of Tmem 33, Pgm1, Eif3f, Rps24, Cct8, Hsd17b4, Aldh3a1, Ddost, Aldh3a1, Eif3c, Luc7l2, and Acadvl—proteins with known roles in hearing loss [ 99 ]. Using an ischemia and reperfusion model in C57BL/6 mice, a study by Hao et al discovered that delivery of NPC-EVs transfected with miR-21 to these mice reduced caspase-3/parvalbumin expression, increased IL-10 expression, and prevented an increase in TNF-α and IL-1β expression of cochlear hair cells [ 103 ]. This suggests that delivery of EV-miR-21 could serve to improve outcomes of cochlear damage related to ischemia [ 103 ].…”
Section: Role Of Evs In Diseases Of the Ear Nose And Throatmentioning
confidence: 99%
“…Using an ischemia and reperfusion model in C57BL/6 mice, a study by Hao et al discovered that delivery of NPC-EVs transfected with miR-21 to these mice reduced caspase-3/parvalbumin expression, increased IL-10 expression, and prevented an increase in TNF-α and IL-1β expression of cochlear hair cells [ 103 ]. This suggests that delivery of EV-miR-21 could serve to improve outcomes of cochlear damage related to ischemia [ 103 ]. Another in vivo report found that, compared with normoxic bone marrow mesenchymal stem cells (BMSCs), hypoxic BMSCs reduced cisplatin-induced ototoxicity by upregulating HIF-1α, superoxide dismutase 1 (SOD1), and SOD2 expression [ 104 ].…”
Section: Role Of Evs In Diseases Of the Ear Nose And Throatmentioning
confidence: 99%